5‐ALA/SFC Attenuated Binge Alcohol–Induced Gut Leakiness and Inflammatory Liver Disease in HIV Transgenic Rats. (13th June 2019) - Liu, Chi; Zhu, Ping; Fujino, Masayuki; Zhu, Shuoji; Ito, Hidenori; Takahashi, Kiwamu; Nakajima, Motowo; Tanaka, Tohru; Zhuang, Jian; Li, Xiao‐Kang
Abstract : Background: This study aimed to investigate the protective effect of 5‐aminolevulinic acid (5‐ALA) and sodium ferrous citrate (SFC) against binge alcohol–induced gut leakiness and inflammatory liver disease in HIV transgenic (TG) rats. Methods: TG rats were treated with 3 consecutive doses of binge ethanol (EtOH) with or without 5‐ALA/SFC. Blood and liver tissue samples were collected at 6 hours following the last dose of EtOH. Results: Compared with the wild‐type (WT) rats, the TG rats showed increased sensitivity to alcohol‐mediated inflammation, as evidenced by the significantly elevated levels of serum endotoxin, AST, ALT, ED1, and ED2 staining in liver. In contrast, 5‐ALA/SFC improved the above biochemical and histochemical profiles. 5‐ALA/SFC also attenuated the up‐regulated mRNA expression of leptin and CCL2. Furthermore, down‐regulated intestinal ZO‐1 protein expression was also inhibited by 5‐ALA/SFC. Moreover, the expressions of HO‐1, HO‐2, Sirt1, and related signal transduction molecules in liver were increased by 5‐ALA/SFC. These results demonstrated that 5‐ALA/SFC treatment ameliorated binge alcohol exposure liver injury in a rat model of HIV‐infected patients by reducing macrophage activation and expression of inflammatory cytokines/chemokines, and by inducing HO‐1, HO‐2, and Sirt1 expression. Conclusions: Taken together, these findings suggested that treatment with 5‐ALA/SFC has a potential therapeutic effect for binge alcohol exposure liver injury in HIV‐infected patients. Abstract : Protective effect of 5‐ALA and SFC against binge alcohol‐induced gut leakiness and inflammatory liver disease in HIV transgenic rats which are model of HIV‐infected patients was investigated. 5‐ALA/SFC treatment improved biochemical and histochemical profiles, attenuated the up‐regulated mRNA expression of leptin and the downstream target chemokine CCL2, increased the expressions of HO‐1, HO‐2, Sirt1 in liver, and inhibited down‐regulated intestinal ZO‐1 expression. These results suggested a potential therapeutic effect for binge alcohol exposure liver injury in HIV patients.